The Influence of Service Quality, Security, and Product Features on User Customer Satisfaction BRImo Application (Study of BRImo Application Users in Madiun Regency) - Alodiya Sifa Meiyantika; Yuniardi Rusdianto (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to explore the relationship between product features, security, and service quality and customer satisfaction among BRImo application users in Madiun Regency. This study used quantitative research methodology along with techniques from descriptive analysis. Researchers employed a purposive sampling method in conjunction with a sample technique in this study. The group under research is made up of Madiun residents who have used the BRImo application to perform online transactions. Based on the study done, it was found that, partially and concurrently, product features, security, and service quality all had a significant positive impact on customer satisfaction among BRImo application users in Madiun Regency.